2006
DOI: 10.1021/la061107o
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Active Silica Nanoparticles. Part 1. Electrochemistry and Catalytic Activity of Spherical, Nonporous Silica Particles with Nanometric Diameters and Covalently Bound Redox-active Modifications,

Abstract: Nonporous spherical silica nanoparticles resulting from a controlled Stöber process are covalently surface modified with redox-active molecules. Ferrocene, a ruthenium(II) complex with an N2P2Cl2 ligand set, and a sterically hindered biphenylamine are used as modifiers. The resulting materials are characterized by physical, spectroscopic, electrochemical, and chemical methods. The cyclic voltammetric behavior is studied in detail and reveals effects of charge transport by electron hopping along the surface of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 40 publications
2
28
1
Order By: Relevance
“…Dai et al [43] reported the acceleration of electron transfer by SBA-15 type mesoporous materials to the surface of electrode. In the similar lines results were obtained in the other series of mesoporous silica [44][45][46] and this can be ascribed to the electron hopping mechanism that aid for the electron transfer inside silica mesopores [43,[47][48][49].…”
Section: Confirmation Of the Presence Of Europium Ionsupporting
confidence: 83%
“…Dai et al [43] reported the acceleration of electron transfer by SBA-15 type mesoporous materials to the surface of electrode. In the similar lines results were obtained in the other series of mesoporous silica [44][45][46] and this can be ascribed to the electron hopping mechanism that aid for the electron transfer inside silica mesopores [43,[47][48][49].…”
Section: Confirmation Of the Presence Of Europium Ionsupporting
confidence: 83%
“…Nanosilica has been widely used as inorganic filler in many polymeric materials, for it has been regarded as a promising material that can be functioned through the active hydroxyls on its surface [24][25][26][27][28][29][30][31]. However, literature concerning application of nanosilica-grafted aromatic amine as immobilized antioxidant for SBR is finite.…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of ferrocene‐terminated indium tin oxide,33 gold,34 and silica3537 particles was reported recently. In particular, monodisperse and nonporous spherical Stöber silica particles are well established as solid supports3842 and provide a defined geometry and surface environment. Under thoroughly controlled reaction conditions, spheres with predictable diameters are formed 41…”
Section: Introductionmentioning
confidence: 99%